2023
DOI: 10.1108/ijopm-05-2022-0314
|View full text |Cite
|
Sign up to set email alerts
|

Supply networks for extreme uncertainty: a resource orchestration perspective

Abstract: PurposeDisasters are growing in frequency and scale, unmasking the systemic vulnerabilities of modern supply chains and highlighting the need to understand how to respond to such events. In the context of an extreme event such as the COVID-19 pandemic, this research focuses on how networks of organizations leverage their combined resources and capabilities to develop, manufacture and deliver new products outside their traditional markets.Design/methodology/approachFollowing a theory elaboration process, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Supply chains are increasingly being weaponized by embargoes and sanctions (Farrell and Newman, 2022; Browning et al ., 2023), as external institutional and consumer influences necessitate companies to unhook from conflict zones, countries or regimes. We hope that the research questions, vectors and areas suggested can inspire OM scholars to develop research for understanding these unhooking strategies that decouple operations from conflict zones and actors, including the implications of the fragmentation of supply chains, adding to the literature on supply network design (Skipworth et al ., 2023) and resilience (Vega et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supply chains are increasingly being weaponized by embargoes and sanctions (Farrell and Newman, 2022; Browning et al ., 2023), as external institutional and consumer influences necessitate companies to unhook from conflict zones, countries or regimes. We hope that the research questions, vectors and areas suggested can inspire OM scholars to develop research for understanding these unhooking strategies that decouple operations from conflict zones and actors, including the implications of the fragmentation of supply chains, adding to the literature on supply network design (Skipworth et al ., 2023) and resilience (Vega et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to fully unhook supply chains may be slowed down due to rigid mental models of managers and the low adaptability of supply networks (Lee, 2004). This tension is leading to reconfiguration or the ability to rearrange the key “elements” of the supply chain (Skipworth et al ., 2023; Vega et al ., 2023). The development of an alternative permutation from the current state (Srai and Gregory, 2008, p. 394), in a conflict of international scale, is our novel context in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, ROT highlights the systematic approach to structuring resource collections, combining them into configurations and finally leveraging the configurations for firm performance (Burin et al, 2020;Saccani et al, 2023). ROT is fast becoming a theory of choice for supply chain researchers in areas such as supply chain integration (Liu et al, 2016), lean and green supply chain (Feng et al, 2018), supply chain transparency (Gligor et al, 2022), supply chain flexibility (Burin et al, 2020), supply chain resilience and robustness (Eel baz et al, 2023), product launch performance (Jenkins et al, 2023), supply networks (Skipworth et al, 2023), circular supply chain (Saccani et al, 2023) and green purchasing (Kwabena Anin et al, 2023).…”
Section: Resource Orchestration Theorymentioning
confidence: 99%
“…Scholars suggest that it would be sufficient to consider around 4-10 cases (Eisenhardt, 1989(Eisenhardt, , 2007Skipworth et al, 2023;Ellegaard et al, 2022), but due to the complexity of the research topic, we determined the final number of cases with theoretical saturation in mind. Specifically, we reached theoretical saturation after a purposive sample of 15 cases (Lincoln and Guba, 1985;Yin, 2013) involving a total of 51 interviews.…”
Section: The Samplementioning
confidence: 99%